Distributed architecture to enhance systems protection against unauthorized activity via USB devices - Oliveira, José (2021)
Cyberattacks exploiting Universal Serial Bus (USB) interfaces may have a high impact on individual and corporate systems. The BadUSB is an attack where a USB device’s firmware is spoofed and, once mounted, allows attackers to execute a set of malicious actions in a target system. The countermeasures against this type of attack can be grouped into two strategies: phyiscal blocking of USB ports and software blocking. This paper proposes a distributed architecture that uses software blocking to enhance system protection against BadUSB attacks. This architecture is composed of multiple agents and external databases, and it is designed for personal or corporate computers using Microsoft Windows Operating System. When a USB device is connected, the agent inspects the device, provides filtered information about its functionality and presents a threat assessment to the user, based on all previous user choices stored in external databases. By providing valuable information to the user, and also threat assessments from multiple users, the proposed distributed architecture improves system protection.